(untitled) (Педагогіка вищої та середньої школи, 2003)
In article some aspects of a role and a place of means o f training are considered in the them o f their complex use at the high technical school. The terminological review and comparative classification of means o f training and their offered classification by ergonomic and technical properties. Results of expert interrogation which finds out priorities in a choice of means training at diffèrent stages of lesson are given.